Greenwashing and the Nature of Education in Relation to Consumer Trust in Fast Fashion Marketing Communication - Marko, Marianna; Kusá, Alena (Communication Today, 2023)
The fashion industry has long been known as one of the most polluting industries in the world. The urgent need to improve the current critical situation has given rise to a number of global initiatives, organisations and movements that highlight and at the same time, are involved in the sustainability of the fashion industry. As pressure from consumers and businesses is constantly growing, fast fashion brands are introducing their own sustainable fashion collections which, however, are likely to deceive consumers and, when combined with green marketing, are merely used just to reach their business goals. Environmental education as a key determinant is the way to eliminate deception and properly assess messages by consumers. The main goal of the study is, through neuromarketing research, to define the impact of the studied sample of informed and uninformed consumers from Generations Y and Z when it comes to customer loyalty to the marketing communication of fast fashion brands.